A educação domiciliar no cenário brasileiro - Maria Celi Chaves Vasconcelos; Bruno Antonio Picoli (Desidades, 2020)
With the restriction of school activities imposed by the COVID-19 pandemic, the recent debate about the regulation of homeschooling has gained even more relevance. The interviewee reveals data from her studies, which help to clarify the demand for a legislation that supports families that, for a number of reasons, opt for this modality of education. Formal, economic and religious aspects at stake are discussed, as well as the role of the State and family. Information on the singularity of the brazilian context is brought forward, in comparison with other countries and other moments in history. Lastly, the necessity of not treating education in schools and homeschooling as opposite or exclusionary is emphasized, as well as the fact that in the brazilian case, because of everything that the school represents, education in schools is still fundamental.